Skilled migrants and labour market integration: How important is the selection process? - Justin William VanDeVen; Sarah Voitchovsky (IZA Journal of Migration, 2015)
Although many OECD countries use skilled migration to boost economic performance, there is surprisingly little direct empirical evidence concerning what effects historical initiatives in this area have had. This study estimates the effects of Australia's recent shift toward a "hybrid approach" for managing economic migration, which increased the requirements for (supply-driven) independent skilled migrants at the same time that (demand-driven) employer-sponsored migration was expanded. We find that this combination of policy adjustments substantively improved short-term employment outcomes amongst skilled migrants six months after taking up permanent residency.
Keywords: J15; J61; J24; 330; Skilled migration; Australia; Migrant employment outcomes; Difference-in-differences